Attitudes toward, and awareness of, online privacy and security: a quantitative comparison of East Africa and U.S. internet users - Ruhwanya, Zainab Said (Kansas State University, 2015)
The increase in penetration of Internet technology throughout the world is bringing an increasing volume of user information online, and developing countries such as those of East Africa are included as contributors and consumers of this voluminous information. While we have seen concerns from other parts of the world regarding user privacy and security, very little is known of East African Internet users’ concern with their online information exposure. The aim of this study is to compare Internet user awareness and concerns regarding online privacy and security between East Africa (EA) and the United States (U.S.) and to determine any common attitudes and differences. The study followed a quantitative research approach, with the EA population sampled from the Open University of Tanzania, an open and distance-learning university in East Africa, and the U.S. population sampled from Kansas State University, a public university in the U.S. Online questionnaires were used as survey instruments. The results show no significant difference in awareness of online privacy between Internet users from East Africa and the U.S. There is however, significant difference in concerns about online privacy, which differ with the type of information shared. Moreover, the results have shown that the U.S. Internet users are more aware of online privacy concerns, and more likely to have taken measure to protect their online privacy and conceal their online presence, than the East African Internet users. This study has also shown that East Africans Internet users are more likely to be victims of online identity theft, security issues and reputation damage.
Keywords: Privacy; Security; Data protection and privacy law; Online Privacy; Cyber security; Internet; Computer Science (0984); Information Technology (0489); Sub-Saharan Africa Studies (0639)